Nitrogen addition pulse has minimal effect in big sagebrush (Artemisia tridentata) communities on the Pinedale Anticline, Wyoming (USA). - Christopher W Beltz; Megan L Mobley; Ingrid C Burke (PLoS ONE, 2019)
Nitrogen additions are known to elicit variable responses in semi-arid ecosystems, with responses increasing with precipitation. The response of semi-arid ecosystems to nitrogen are important to understand due to their large spatial extent worldwide and the global trend of increasingly available nitrogen. In this study, we evaluated the impact of a single nitrogen addition pulse on a semi-arid big sagebrush (Artemisia tridentata) ecosystem in western Wyoming. This is important given that sagebrush ecosystems are poorly understood, despite their prevalence in the western US. In addition, large-scale nitrogen additions have begun on sagebrush landscapes in Wyoming in order to mitigate population declines in mule deer (Odocoileus hemionus). The study objectives were (1) to evaluate the effectiveness of a nitrogen fertilization pulse in increasing sagebrush biomass and forage quality, and (2) to assess effects of nitrogen addition on soil biogeochemistry and vegetation community structure. We fertilized 15 plots across 5 locations in western Wyoming using a single pulse of urea (5.5g N m-2). In addition, we immobilized available nitrogen through surface hay treatments (250g hay/m2). Nitrogen additions failed to increase growth of sagebrush, alter nitrogen content of sagebrush leaders, or alter greenhouse gas efflux from soils. The plant community also remained unchanged; total cover, species richness, and community composition were all unaffected by our treatment application. Over the two years of this study, we did not find indications of nitrogen limitation of ecosystem processes, despite a wet growing season in 2014. Thus, we have found a general lack of response to nitrogen in sagebrush ecosystems and no treatment effect of a single pulse of N to sagebrush biomass or forage quality.